ANALISIS PENGARUH STORE ATMOSPHERE TERHADAP MINAT BELI KONSUMENDI INDOMARET KOTA MATARAM - SOPAN SOPIAN HADI (Master of Management, Mataram University, 2015)
This study aims to investigate the influence of store atmosphere, which consists of anumber of variable such as exterior, interior store layouts and pointr of interest display, onthe consumers interest to purchase in the Indomaret store in Mataram City. This study usesthe theories of marketing management related to store atmosphere and consumers interest topurchase.This study employed an associative approach. A purposive sampling method wasused to collect data from 100 respopndents who had already visited Indomaret stores inMataram City. The instruments for data collection were a questionnaire and documentationstudy. The data collected were analyzed with a multiple linear regression method.Result of the study show that the variable of general interiot of MataramIndomaretstores influenced very significantly on the counsumers interest to buy. Meanwhile, othervariables, such as the shop exterior, store layout, and interior displays a point of interest, didnot affect the consumers interest tu buy.Key word : store atmosphere, eksterior toko, store layout, interior point of interest display